Evaluating the Effectiveness of the Enrichment Program in English using Sign Language of Deaf Students - Zaien, Sahar Zedan; Habbash, Manssour (Journal of Educational and Psychological Sciences, 2020)
Deaf and hard of hearing students are at disadvantage in standard learning environment resultantly their academic performance is poor as compared to normal peers. The current study evaluated a newly designed English Language Enrichment Program with the help of American Sign Language as the medium of instruction at Community College of the University of Tabuk. In this quantitative experimental study 20 female deaf students were divided randomly, 10 in experimental and 10 in the control group. The Enrichment Program was administered to the students in the experimental group, however, no Enrichment Program was delivered to the control group. After the program, both groups took an assessment test to demonstrate the efficiency of ELEP. The results revealed that the academic performance of the experimental group significantly improved as compared to that of the control group. The current study provided a framework for future studies to design and implement Enrichment Programs to uplift the learning process among deaf and hard of hearing students.